Uji Preferensi Hama Kepik Hijau Nezara viridula L. (Hemiptera:Pentatomidae) pada Tanaman Kacang Kedelai dan Kacang Panjang di Laboratorium - Silvia Samosir; Marheni Sembiring; Syahrial Oemry (Jurnal Agroekoteknologi, 2015)
The objectives of the research was to know the preferences of stink bug (N. viridula) on soybean plant and long bean in screenhouse. This research was conducted in the screenhouse Faculty of Agriculture University of Sumatera Utara from April until July 2014. This method used Block Randomized Design (BRD) nonfactorial with two treatments soybean and long bean, respectively with nine replications. The results showed that N. viridula prefer soybean than long bean. The highest number of adults N. viridula (10.17 head) on K1. The highest index attack percentage (83.95%), most attack symptoms, and the highest number of eggs N. viridula (31.56 grain) on soybean while the highest number of nymphs (9.67 head) on long bean.Key words: preferences, Nezara viridula, soybean, long bean.